Protein supplementation improves muscle mass and physical performance in undernourished prefrail and frail elderly subjects: a randomized, double-blind, placebo-controlled trial - Park, Yongsoon; Choi, Jeong-Eun; Hwang, Hwan-Sik (The American journal of clinical nutrition, 2018)
Age-related loss of muscle mass and function is a major component of frailty. Nutrition supplementation with exercise is an effective strategy to decrease frailty by preventing sarcopenia, but the effect of protein alone is controversial. The present study was performed to investigate a dose-dependent effect of protein supplementation on muscle mass and frailty in prefrail or frail malnourished elderly people. A 12-wk double-blind randomized controlled trial was conducted in elderly subjects aged 70-85 y with ≥1 of the Cardiovascular Health Study frailty criteria and a Mini Nutritional Assessment score ≤23.5 (n = 120). Participants were randomly assigned to 1 of 3 groups: 0.8, 1.2, or 1.5 g protein · kg-1 · d-1, with concealed allocation and intention-to-treat analysis. Primary outcomes were appendicular skeletal muscle mass (ASM) and skeletal muscle mass index (SMI) measured by dual-energy X-ray absorptiometry. After the 12-wk intervention, the 1.5-g protein · kg-1 · d-1 group had higher ASM (mean ± SD: 0.52 ± 0.64 compared with 0.08 ± 0.68 kg, P = 0.036) and SMI (ASM/weight: 0.87% ± 0.69% compared with 0.15% ± 0.89%, P = 0.039; ASM/BMI: 0.02 ± 0.03 compared with 0.00 ± 0.04, P = 0.033; ASM:fat ratio: 0.04 ± 0.11 compared with -0.02 ± 0.10, P = 0.025) than the 0.8-g protein · kg-1 · d-1 group. In addition, gait speed was improved in the 1.5-g protein · kg-1 · d-1 group compared with the 0.8-g protein · kg-1 · d-1 group (0.09 ± 0.07 compared with 0.04 ± 0.07 m/s, P = 0.039). There were no significant differences between the 1.2- and 0.8-g protein · kg-1 · d-1 groups in muscle mass and physical performance. No harmful adverse effects were observed. The present study indicates that protein intake of 1.5 g · kg-1 · d-1 has the most beneficial effects in regard to preventing sarcopenia and frailty compared with protein intakes of 0.8 and 1.2 g · kg-1 · d-1 in prefrail or frail elderly subjects at risk of malnutrition. This trial was registered at cris.nih.go.kr as KCT0001923.